La auditoría tributaria para la correcta determinación del impuesto sobre las ventas (2024)
This paper exposes the extent to which the application of the tax audit has an impact on the determination and payment of the Value Added Tax (VAT) in a company in the commercial sector of the municipality of Palmira.